HUBUNGAN KARAKTERISTIK IBU DENGAN PEMBERIAN ASI EKSKLUSIF DI WILAYAH KERJA PUSKESMAS KORPRI KECAMATAN BERASTAGI KABUPATEN KARO TAHUN 2019 - Edy Marjuang Purba (CHMK HEALTH JOURNAL, 2020)
Exclusive breastfeeding is breastfeeding since the baby is approved until the baby is given 6 months. Coverage of exclusive breastfeeding in infants 0-6 months in Indonesia in 2013 was 54.3%. This figure is still far from the target that must be achieved exclusive breastfeeding at 80%. Based on this reason, it is necessary to research the relationship of characteristics, knowledge and attitudes of mothers with exclusive breastfeeding. This type of research is analytic research with cross sectional design. Data analysis using chi square test with a sample of 85 mothers who have babies receiving 7-12 months. This study aims to look at the relationship of characteristics, education, work, discussion and parity, knowledge and attitudes of mothers with exclusive breastfeeding conducted in the Work Area of ​​the Korpri Health Center in Berastagi Sub-district. The results showed that there was a relationship between age (p = 0.001), parity (p=0.0001), knowledge (p=0.002) and attitude (p=0.0001) and exclusive breastfeeding. There was no relationship between the education (p= 0.736), occupation (p=0.286), assistance (p= 0.638). Suggested to the midwives' special health workers to increase information assistance through counseling, disseminating media such as leaflets to the community and motivating maternity mothers and who reviewed their assessment to the puskesmas to provide exclusive breastfeeding to their babies.